Science, policy, and stakeholders in water management : an integrated approach to river basin management - Gooch, Geoffrey D.; Stålnacke, Per (Earthscan, 2010)
One of the major problems facing practitioners and scientists working with water management is how to integrate knowledge and experiences from scientific, policy and stakeholder perspectives. In this book this science-policy-stakeholder interface (SPSI) is examined both analytically and through the description of practical experiences from river basins in Europe, India and South-East Asia. These include the Tungabhadra (India), Sesan (Vietnam/Cambodia), Tagus (Spain/Portugal) and Glomma (Norway), which particularly highlight issues associated with pollution, severely altered river flows and tr.